Reimaginando a saúde mental: o fazer alma e a possibilidade de novos caminhos - Luciana Ximenez (International Journal of Education and Health, 2026)
INTRODUCTION: The article proposes a reimagining of mental health pathways based on James Hillman’s archetypal psychology, shifting the focus from the elimination of symptoms to their recognition and appreciation. In contrast to the biomedical model, which seeks to correct dysfunctions and restore an ideal of normality, the archetypal perspective introduces the concept of “soul-making”, in which imagination plays a central role. Imagination is understood as an act capable of transforming events into experiences, generating meaning and expanding psychic reality. DEVELOPMENT: Within this framework, the concept of “pathologizing” is presented as a legitimate function of the psyche, producing suffering, disorder, and abnormality as forms of expression of the soul. Symptoms are no longer seen as deviations to be eliminated, but as symbolic manifestations connected to individuation and singularity. Conditions such as anxiety and depression, therefore, may be understood as responses to contemporary cultural demands rather than merely adaptive failures. The text also highlights the role of the daimon as a guiding force in psychic life, manifesting through affects and symptoms, often beyond the control of the ego. Individuation, in this sense, expresses not only personal realization but also an impersonal dimension that calls for recognition. CONCLUSION: Finally, the author argues that mental health practice should create spaces for the experience and symbolization of suffering, resisting homogeneous ideals of happiness and normality.